Land use change in Kelantan: review of the Environmental Impact Assessment (EIA) reports - Mohamad Shaharudin Samsurijan; Nik Norulaini Abd Rahman; Muhammad Izzuddin Syakir Ishak; Tajul Ariffin Masron; Omar Kadir (Penerbit Universiti Kebangsaan Malaysia, 2018)
Environmental Impact Assessment (EIA) is an essential process in minimizing the adverse environmental impact and to ensure sustainable land use. In Malaysia, under Section 34A, Environmental Quality Act 1974, the EIA was made compulsory for any project that can be a threat to the environment. All EIA reports require approval from the Department of Environment prior to the project commencement. This study argues that land use change for agriculture and logging in Kelantan has a direct connection on the approved EIA. The objectives of this study is to identify a list of EIA reports that have been previously approved in Kelantan since 2000 to 2015; and to analyze the EIA reports embracing the trends of approval, the type of project, territory involved, the consultant involved, the time of approval, potential impacts and mitigation measures. This study had been reviewed 192 EIA report in DOE Kelantan and covered year 2000 to 2015. The review process to look at the type of project, territory involved, the consultant involved, the time of approval, potential impacts and mitigation measures. It’s covered three district of Tanah Merah, Kuala Krai and Gua Musang. To date, a total of 222 EIA reports have been approved in Kelantan. The results showed a notable increment in the approval trend of EIA reports. A total of 149 conducted EIA projects are fall within the territory of Gua Musang. Majority of the approvals are granted to agriculture and logging projects. Majority projects have passed over the area of secondary forest, oil palm and rubber plantations, permanent reserve forest and the watershed of tributaries of Sungai Kelantan. Land-clearing activities for agriculture and logging on a large scale have a significant impact to environmental change in Kelantan.